ECONOMIC EFFICIENCY OF GROWING NEW DOMESTIC VARIETIES OF WINTER WHEAT AT DIFFERENT SOWING PERIODS IN THE WESTERN FOREST STEPPE OF UKRAINE (INNOVATIVE ECONOMY, 2024)
Yashchuk T.S., Samets N.P., Hrytsevych Yu.S., Muzykа O.M. ECONOMIC EFFICIENCY OF GROWING NEW DOMESTIC VARIETIES OF WINTER WHEAT AT DIFFERENT SOWING PERIODS IN THE WESTERN FOREST STEPPE OF UKRAINEPurpose. To study and evaluate the impact of sowing dates of modern varieties of winter wheat on productivity, grain quality, production profitability in the agrobiological system of cultivation in the Western Forest Steppe zone.Methodology of research. Field: observation of the growth and development of plants during the growing season, yield formation; laboratory: determination of grain quality indicators; mathematical and statistical: dispersion analysis; calculation-comparative: determination of productivity, economic assessment of the researched elements of technology.Findings. Effective technological elements of the agrobiological system of growing grain ear crops have been developed in relation to the terms of sowing winter wheat in the conditions of the Western Forest Steppe of Ukraine.It is substantiated that in the conditions of climate change and in these soil and climatic conditions, winter wheat shows high indicators for late sowing, the best dates for sowing winter wheat are September 25 and October 5. A trend of growth in grain quality indicators for late sowing was noted. The content of gluten and protein in winter wheat grains, on average for 2021–2023, taking into account the data for all varieties, was the highest for its sowing in the latest dates (October 15 and 25) and amounted to 20.1% and 20.8% for gluten and 11.4; 11.7% for protein. It has been proven that the sowing of winter wheat in the period from September 25 to October 5 ensured the highest yield of quality grain 6.70–7.10 t/ha, conditionally net profit – 11900– 12384 UAH/ha, profitability level – 54,6–56,7%.Originality. The technological elements of ensuring the sustainability of winter wheat grain production with valuable economic characteristics have been developed, which contributes to increasing its competitiveness and profitability based on the use of the biological potential of new varieties in the conditions of the Western Forest Steppe.Practical value. The implementation of effective technological elements of the agrobiological system of growing grain ear crops in the conditions of the Western Forest Steppe will contribute to the growth of high-quality grain yield of new varieties of winter wheat, which will ensure a decrease in the cost of production and an increase in its profitability.Key words: grain ear crops, variety, sowing period, productivity, quality, competitiveness, profitability.
Keywords: grain ear crops; variety; sowing period; productivity; quality; competitiveness; profitability.